Knowledge about Human Papillomavirus Infection and Vaccine of the 4th - 6th year Medical Students and Internships at Srinagarind Hospital - Bumroongsawat, Paramet; Pratipanawatr, Chaiyaporn; Jandarak, Worada; Chotchai, Nonpavit; Charoenthanadhol, Thanakorn; Phetnadi, Jirameth; Thepwongsa, Isaraporn; Luvira, Varisara (Srinagarind Medical Journal, 2018)
Background and objective: In December 2016, the Department of disease control has added Human-papillomavirus (HPV) vaccine into the national list of essential medicine. Because HPV vaccine is a new issue, there is still the limitation of knowledge for normal practice. Knowledge of HPV infection and vaccine are important for physicians to be able to give information and advice the patients and population. Major objective of this study, therefore, was to evaluate the knowledge about these topics of the forth to sixth year medical students and internships at Srinagarind hospital. Methods: A descriptive study was conducted in the population of 452 forth to sixth year medical students and 82 internships. The sample size were 111 forth to sixth year medical students and 56 internships. The systematic sampling was done, use a self-administered questionnaire for evaluating the knowledge. The results were described as central tendency, frequency and percentage. Results: The median of study subjects age was 23. Percentage of male was 58.4. Response rate was 82.0 percent. From the total score of 19,the median score of forth to sixth year medical students was 11.0 (95%CI: (11.0, 11.0) with IQR of 4.0. The mean score of internships was 11.7 (95%CI: (10.7, 12.7) with S.D. of 9.0. 68.7 and 71.4 percent of forth to sixth year medical students and internships have passed the criteria respectively. Conclusion: The proportion of forth to sixth year medical students and internships had sufficient knowledge was about 2 out of 3 in both groups